Biomechanical Assessment of Three Osteosynthesis Constructs by Periprosthetic Humerus Fractures - Harb, Afif (Adv Orthop, 2020)
BACKGROUND: Biomechanical stability assessment of 3 different constructs for proximal fixation of a locking compression plate (LCP) in treating a Worland type C periprosthetic fracture after total shoulder arthroplasty. METHODS: 27 Worland type C fractures after shoulder arthroplasty in synthetic humeri were treated with 14-hole LCP that is proximally fixed using the following: (1) 1 × 1.5 mm cerclage wires and 2x unicortical-locking screws, (2) 3 × 1.5 mm cerclage wires, or (3) 2x bicortical-locking attachment plates. Torsional stiffness was assessed by applying an internal rotation moment of 5 Nm and then after unloading the specimen, an external rotation moment of 5 Nm at the same rate was applied. Axial stiffness was assessed by applying a 50 N preload, and then applying a cyclic load of 250 N, then increasing the load by 50 N each time, until a maximum axial load of 2500 N was reached or specimen failure occurred. RESULTS: With regard to internal as well as external rotational stiffness, group 1 showed a mean stiffness of 0.37 Nm/deg and 0.57 Nm/deg, respectively, group 2 had a mean stiffness of 0.51 Nm/deg and 0.39 Nm/deg, respectively, while group 3 had a mean stiffness of 1.34 Nm/deg and 1.31 Nm/deg, respectively. Concerning axial stiffness, group 1 showed an average stiffness of 451.0 N/mm, group 2 had a mean stiffness of 737.5 N/mm, whereas group 3 had a mean stiffness of 715.8 N/mm. CONCLUSION: Group 3 displayed a significantly higher torsional stiffness while a comparable axial stiffness to group 2.